2019
DOI: 10.1093/braincomms/fcz022
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variability in response to amyloid beta deposition influences Alzheimer’s disease risk

Abstract: Genome-wide association studies of late-onset Alzheimer’s disease risk have previously identified genes primarily expressed in microglia that form a transcriptional network. Using transgenic mouse models of amyloid deposition, we previously showed that many of the mouse orthologues of these risk genes are co-expressed and associated with amyloid pathology. In this new study, we generate an improved RNA-seq-derived network that is expressed in amyloid-responsive mouse microglia and we statistically compare this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
76
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(84 citation statements)
references
References 60 publications
8
76
0
Order By: Relevance
“…These findings confirm previous results in the p25/Cdk5 model of neurodegeneration where a reactive microglia phenotype with activated IFN pathway was found [34]. More recently, Salih et al [33] identified a number of interferon signaling genes to be in co-expression network that is expressed in amyloid-responsive mouse microglia, including Oas and Ifit family members, and transcription factors such as Irf7 and Stat. The authors further found that Alzheimer's disease loci colocalize with cis-eQTLs targeting OAS1 in interferon-γ stimulated iPSC-derived macrophages.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…These findings confirm previous results in the p25/Cdk5 model of neurodegeneration where a reactive microglia phenotype with activated IFN pathway was found [34]. More recently, Salih et al [33] identified a number of interferon signaling genes to be in co-expression network that is expressed in amyloid-responsive mouse microglia, including Oas and Ifit family members, and transcription factors such as Irf7 and Stat. The authors further found that Alzheimer's disease loci colocalize with cis-eQTLs targeting OAS1 in interferon-γ stimulated iPSC-derived macrophages.…”
Section: Discussionsupporting
confidence: 90%
“…Component 22 is highly enriched for a number of genes in the Type 1 interferon-signaling, defense response to virus, and complement activation pathways ( Fig 2E). A number of studies have linked genes from these functional categories to Alzheimer's disease [33][34][35], autism [36,37] and lupus [13]. Interestingly, we discovered that this component is also a trans-eQTL for Alzheimer's disease susceptibility loci (see below).…”
Section: Identification Of Gene Network In Stimulated Monocytes and mentioning
confidence: 86%
“…We observed similar findings in the 5xFAD amyloidogenic model, which exhibited an increase in gene and protein expression levels of Inpp5d with disease progression, predominately in plaque-associated microglia, suggesting induction of Inpp5d in plaqueproximal microglia. Similarly, a recent study reported that Inpp5d is strongly correlated with amyloid plaque deposition in the APPPS1 mouse model [25,26]. These findings are consistent with the observation of microgliosis in both AD and its mouse models.…”
Section: Discussionsupporting
confidence: 86%
“…IFN was shown to be required for sustaining microglial activation since suppression of IFN signaling significantly reduced the levels of CD68 and Clec7a, markers for microglial activation, and shifted the morphology of microglia toward homeostatic form ( Roy et al, 2020 ). Intriguingly, polymorphisms of ISGs, including OAS1 , ITGAM , LAPTM5 , and LILRB4 , were conjointly identified as a significant risk factor for AD, implicating IFN pathway as a genetic modifier ( Salih et al, 2019 ).…”
Section: Antiviral Immune Response In Promoting Ad Pathogenesismentioning
confidence: 99%
“…On the other hand, LOAD is a polygenic disease, where a number of risk polymorphism and rare variants exert their functions from microglia and/or involved in immunity ( Zhang et al, 2013 ; Huang et al, 2017 ; Kunkle et al, 2019 ). The implication of ISGs as risk factor of AD ( Salih et al, 2019 ) together with IFN upregulation in aging brain suggest that IFN pathway may have a profound influence on AD pathogenesis ( Figure 2 ).…”
Section: Contributing Factors To Antiviral Immune Response In Admentioning
confidence: 99%